Hans Rosbaud and the Music of Arnold Schoenberg - Evans, Joan (Canadian University Music Review / Revue de musique des universités canadiennes, 2001)
This study documents the efforts of Hans Rosbaud (1895–1962) on behalf of the music of Arnold Schoenberg. It is largely based on the twenty-year correspondence between conductor and composer, most of which remains unpublished. Rosbaud's efforts already bore fruit during his tenure at Frankfurt Radio in the early 1930s. After the forced hiatus of the Nazi years (during which he worked in Germany and occupied France), Rosbaud achieved an international reputation as the Schoenberg conductor par excellence. His activities on Schoenberg's behalf involved a plan, previously unremarked in the Schoenberg literature, to bring the aging composer back to Germany.